Exploring the Relationship Between Teacher Job Satisfaction, Self-Efficacy, and Student Engagement in Engineering Classrooms - Roy, V I; Janardhanan, K A (Indian Journal of Information Sources and Services, 2025)
Education is the light that drives out the darkness from life and directs attention toward a child’s overall growth. The procedure is tripolar. It entails communication between the instructor, the students, and the community. One important person in the country’s life is the teacher. Since ancient times, the function of the teacher has been seen as crucial in forming society as well as the personalities of the students. They create societies, show the way forward for the country, and preserve the human elements of life. A commonly acknowledged psychological component of working in any field is job satisfaction. Everyman in every field works to reach his goal. Student engagement in engineering classrooms is a multifaceted construct that encompasses emotional, cognitive, and behavioral dimensions, influencing students’ motivation, interest, and participation in learning activities. In engineering education, effective student engagement is essential because it helps students grasp difficult ideas more deeply, develops their critical thinking and problem-solving abilities, and gets them ready for lucrative engineering professions. However, engineering classrooms often pose unique challenges to student engagement, such as high student-to-faculty ratios, complex technical material, and limited opportunities for hands-on learning, highlighting the need for innovative instructional strategies and research-based approaches to enhance student engagement and learning outcomes in engineering education. This study uses a mixed-methods approach to examine the relationship between student engagement, instructor job satisfaction, and self-efficacy in engineering classrooms. The study will investigate how teacher self-efficacy and work satisfaction affect student engagement and pinpoint the elements that affect both student outcomes and teacher wellbeing. The results of this study will influence the creation of evidence-based tactics to improve teaching and learning outcomes in engineering education by offering insightful information to educators, administrators, and legislators.